宿泊型産後ケアにおける助産師のケアの質指標の開発 - 青島 恵美子; 島袋 香子 (日本母性看護学会誌, 2025)
This study examined the appropriateness, importance, and feasibility of a proposed quality indicator of midwifery care in stay-type postpartum care (hereafter referred to as “quality indicator”), and develop a quality indicator.Based on previous research, a draft quality indicator was created, its appropriateness was reviewed during an expert meeting, and Quality Indicator ver. 1 was developed. Subsequently, 108 midwives were asked to examine the importance and feasibility of Quality Indicator ver. 1 using the Delphi method. Seventy-four and 61 valid responses were obtained for the primary and secondary surveys, respectively. All items met the agreement criteria in terms of importance, but opinions did not converge on the feasibility of one item. Importance and feasibility of Quality Indicator ver. 2, comprising 83 items, was supported. These included seven items for “promotion of mothers’ physical recovery and response to sudden changes,” seven items for “support for mothers’ feelings and mother–child relationship,” three items for “understanding and caring for mothers’ desire to be cared for”, and two items for “confirmation and understanding of mothers child-rearing experiences.” We believe that the newly developed quality indicators can be used for the self-evaluation of midwives after further review. 本研究の目的は、宿泊型産後ケアにおける助産師のケアの質指標（以下、質指標）案の適切性、重要性、実行可能性を検討し、質指標を開発することである。先行研究をもとに質指標案を作成し、専門家会議で適切性を検討、質指標ver. 1を作成した。その後、助産師108名にデルファイ法を用いて質指標ver. 1の重要性、実行可能性を検討した。１次調査74名、２次調査61名の有効回答を得た。すべての項目で重要性の合意基準は満たしたが、１項目の実行可能性の合意が得られなかった。最終的に、Ⅰ母親の身体回復の促進と急変時の対応 ７項目、Ⅱ母親の心と母子関係の支援 ７項目、Ⅲ「大事にされたい」母親の気持ちの受けとめとかかわり ３項目、Ⅳ母親の被養育体験の確認と理解 ２項目等、83項目で構成する質指標ver. 2の重要性と実行可能性が支持された。検討を重ねることで助産師の自己評価に活用できると考える。